Structural function development for electromagnetic interactions in the system of multiple resonant magnetodielectric spheres - Kozar, A. I. (Begell House, 2005)
An approach to derive structure functions of electromagnetic interactions in the system of multiple resonant magnetodielectric spheres is considered. Expressions for magnitic and electrical-type tensor functions of electromagnetic interactions in the system of spheres are obtained, the expressions for structure functions of magnetic and electric type are analyzed.
Keywords: electromagnetic interections; magnetodielectric spheres; structural function